Assessment of the Quality of a Compounded Multivitamin Syrup for Children: Development of Analytical Procedures - A. S. Sutaykina; N. A. Krishtanova; E. V. Vishnyakov; T. D. Sineva (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The range of liquid multivitamins for toddlers approved in the Russian Federation comprises two imported syrups. Pharmacy compounding of vitamin syrups will meet the demand for optimally formulated multivitamins in the pharmaceutical market. Therefore, a necessary step for their release into medical practice is to develop and validate analytical procedures for assessing the quality of such medicinal products.AIM. This study aimed to select and adapt analytical procedures for assessing the quality of a compounded multivitamin product for children.MATERIALS AND METHODS. The study focused on a compounded sorbitol syrup containing vitamins C, PP, B1, B2, and B6. The quantities of vitamin components in the syrup corresponded to the recommended daily intake for children aged 1–3 years. For identification, the authors used qualitative reactions and spectrophotometry. Indicator-free direct iodometry was selected for the quantitative determination of ascorbic acid. Alkalimetry with bromothymol blue was used to quantitate nicotinic acid in the presence of ascorbic acid, pyridoxine hydrochloride, and thiamine hydrochloride. The sum of thiamine hydrochloride and pyridoxine hydrochloride was determined by direct argentometry (Fajans method) with bromophenol blue in an acetic acid medium.  Riboflavin quantification involved visible spectrophotometry at 445 nm and spectrofluorometry. The sorbitol content was measured by refractometry, and the calculations accounted for the content of other syrup components. The validation was conducted in line with the applicable pharmacopoeial requirements (State Pharmacopoeia of the Russian Federation).RESULTS. The authors selected analytical procedures for the quality evaluation of the multivitamin syrup containing five water-soluble vitamins (С, РР, В1, В2, В6) and sorbitol. These analytical procedures were adapted to the simultaneous presence of riboflavin, ascorbic acid, nicotinic acid, thiamine hydrochloride, and pyridoxine hydrochloride. The authors developed analytical procedures for the determination of riboflavin by spectrofluorometry and spectrophotometry and for the selective determination of thiamine hydrochloride by photometry after a precipitation reaction with Reinecke’s salt. The analytical procedure for the determination of riboflavin by spectrofluorometry was validated for specificity, accuracy, linearity, precision (repeatability and intermediate precision), and range.CONCLUSIONS. The study confirmed the applicability of the analytical procedures that were selected and adapted for all components of the multivitamin syrup. The authors identified the conditions for the selective determination of thiamine hydrochloride by spectrophotometry after a precipitation reaction with Reinecke’s salt. The analytical procedure for the quantitative determination of riboflavin by spectrofluorometry was validated and considered suitable for use in analytical laboratories for the quantitative determination of riboflavin in multivitamin mixtures and for syrup stability testing.